Osteoarthritis and cardiovascular disease: A Mendelian randomization study - Wang, Zhao; Kang, Chan; Xu, Pai; Zhang, Shuyi; Song, Jae Hwang; Wang, Dongyang; Yuan, Shuai; Lee, Hyun Jong; Zhang, Meng; Wang, Zhihui; Sun, Hao; Fan, Ruobing (Frontiers in Cardiovascular Medicine, 2022)
Summary Objective: Osteoarthritis (OA) may be associated with cardiovascular disease (CVD). This Mendelian randomization(MR) study investigated the causal relationship between OA and CVD. Methods: From a genome-wide association study of European ancestry, we selected SNPs for two types of OA, knee osteoarthritis (KOA) and hip osteoarthritis (HOA), as instrumental variables. Later, we retrieved three types of CVD： Coronary heart disease(CHD), heart failure(HF), and stroke statistics. This paper used the traditional inverse variance weighting (IVW) method and other methods to estimate the causality of different results. Heterogeneity tests and sensitivity tests were also applied in this paper. Finally, we conducted a MR analysis in the opposite direction to investigate reverse causality. Results: IVW analysis showed that HOA significantly affected the incidence of HF (OR：1.0675；95%：0.0182 to 0.1125, P=0.0066). HOA significantly affected the incidence of stroke（OR：1.1368；95%：1.0739 to 1.2033, P=9.9488e-06）. CHD could dramatically affect the incidence of KOA （OR：0.9011；95%CI：0.8442 to 0.9619, P=0.0018). The rest of the results were negative. Conclusions: Our results revealed a potential causal relationship between HOA and the risk of HF and a potential causal relationship between HOA and the risk of stroke. Our findings also suggested that CHD has a significant causal relationship to the risk of KOA. This paper may provide new ideas for treating OA and CVD.